Effect of collagenase ointment on a radiofrequency induced abrasive wound - Schellini, Silvana Artioli [UNESP]; Pereira, Ivana [UNESP]; Hoyama, Erika [UNESP]; Pellizzon, Claudia Helena [UNESP]; Padovani, Carlos Roberto [UNESP] (My University, 2008)
• Aim: Radiofrequency is one of the methods used to treat wrinkles and skin lesions, but its application may result in an abrasive wound. The purpose of this study was to evaluate the effect of collagenase ointment on the epithelial healing of an abrasive wound induced by a radiofrequency system. • Methods: An abrasive wound was produced using radiofrequency at the dorsal midline of 30 guinea pigs, which were randomly divided into 2 groups: one group were treated with saline solution and the other group treated with collagenase ointment; both used twice daily. The animals were sacrificed at 1, 7, 15, 30 and 60 postoperative days. Macroscopic, histological and morphometric evaluations were performed and the results were submitted to statistical analysis. • Results: The animals treated with collagenase ointment presented accelerated healing process and less inflammatory cell infiltration than the saline solution treated animals from one to fifteen postoperative days. Morphometric evaluation showed a thicker epidermis and a thinner dermis layer in the saline solution group at one and seven postoperative days, but significant differences between both groups were not observed at thirty and sixty postoperative days. • Conclusion: According to our results the use of collagenase ointment may accelerate the healing process of a radiofrequency induced abrasive wound.
Keywords: Collagenase; Guinea pig; Histology; Radio frequency; Wound healing; collagenase; iruxol; sodium chloride; animal experiment; animal model; animal tissue; controlled study; dermis; drug efficacy; drug mechanism; epidermis; guinea pig; histopathology; inflammatory infiltrate; morphometrics; nonhuman; ointment; radiation injury; radiofrequency radiation; skin abrasion; skinfold thickness; wound; wound healing